استراتيجيات تعلم اللغة الثانية لدى دارسي اللغة العربية في قسم اللغة العربية وآدابها بالجامعة الإسلامية العالمية بماليزيا - Alif Fahmi bin Abdullah (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
Learning strategy is one of the ways utilized by students in the process of attaining successful language acquisition. Students who use certain strategies in learning languages can be good language learners. The purpose of this study is to know the direct strategies and indirect strategies used by Arabic language students during learning this language. This study used qualitative research method with semi-structured interview as the method to collect data. Meanwhile, the research sample consisted of three students who studied Advanced Arabic in IIUM in Semester 1, 2014-2015. This study has identified 26 direct strategies and 20 indirect strategies which had been used by the Arabic language students during learning this langauge. These findings can be used as a guideline for students in order to improve their proficiency in Arabic language. They can also be used as a guideline for teachers in order to know the obstacles faced by students as they learn the Arabic language.